Molecular Characterization of Pathogenic Bacteria in Irrigation Water from Zamfarawa River Jega, Kebbi State, Nigeria - Ibrahim Shehu; Ibrahim U. Fakai; Sadiya Adamu (Darul Yasin Al Sys, 2026)
This study aimed to evaluate the bacterial load and pathogenic bacterial contamination of irrigation water used in Zamfarawa Farms, Jega Town. A total of nine irrigation water samples were collected from three different farms. Bacterial enumeration was conducted using the standard plate count method, while coliform levels were estimated using the Most Probable Number (MPN) technique. Biochemical tests were performed for bacterial identification, and conventional polymerase chain reaction (PCR) followed by agarose gel electrophoresis was used to confirm selected bacterial isolates. The overall mean bacterial count in the irrigation water samples was 5.7 × 10⁸ CFU/mL. Farm A recorded the lowest bacterial load, followed by Farm B, while Farm C showed the highest bacterial load. The occurrence data indicated that Salmonella typhi was the most frequently isolated bacterium from Zamfarawa River irrigation water, appearing in 78% of the samples, followed by Bacillus cereus at 22%. Coliform contamination was also detected, with MPN indices of 17 (95% CI: 5–46) in Farms A and C and 14 (95% CI: 4–34) in Farm B, exceeding the reported international standard of 1 log₁₀ CFU/mL. PCR results confirmed the presence of bacterial DNA fragments corresponding to Staphylococcus aureus, Listeria monocytogenes, Bacillus cereus, Salmonella typhi, and Bacillus subtilis. These findings indicate that irrigation water in the study area was contaminated with pathogenic bacteria, likely associated with untreated wastewater, sewage-contaminated water supplies, untreated organic manure, and poor hygiene practices during farming activities. The study concludes that the use of contaminated irrigation water may represent an important route for the transmission of pathogenic microorganisms to agricultural produce and consumers. This study contributes to agricultural microbiology and public health by highlighting the need for routine microbial monitoring, improved wastewater management, and safer irrigation practices in vegetable production systems.